An active matter model captures spatial dynamics of actomyosin oscillations in larval epithelial cells during Drosophila morphogenesis - Euan D. Mackay; Aimee Bebbington; Jens Januschke; Jochen Kursawe; Marcus Bischoff; Rastko Sknepnek (Proceedings of the National Academy of Sciences, 2026)
The apicomedial actomyosin network is crucial for generating mechanical forces in cells. Oscillatory behavior of this contractile network is commonly observed before or during significant morphogenetic events. For instance, during the development of the Drosophila adult abdominal epidermis, larval epithelial cells (LECs) undergo pulsed contractions before being replaced by histoblasts. These contractions involve the formation of contracted regions of concentrated actin and myosin. The emergence and control of pulsed contractions are not fully understood. Here, we combined in vivo 4D microscopy with numerical simulations of an active elastomer model applied to realistic cell geometries and boundary conditions informed by cell polarity to study in vivo subcellular spatial patterns of LEC actomyosin dynamics. The active elastomer model quantitatively reproduced in vivo observations. When compared to rectangular domains, simulations on realistic cell geometries showed systematically better agreement with experiments. We found that cell shape, cell polarity, and organization of the cell’s actomyosin network codetermine spatiotemporal network dynamics both in vivo and in simulations. Furthermore, the model predicted changes to LEC contractile activity under genetic perturbation of the actomyosin network. Our results show that cell geometry, accompanied by boundary conditions which reflect the cells’ polarity, is important to understanding the dynamics of the apicomedial actomyosin network. Moreover, our findings support the notion that spatiotemporal oscillatory behavior of the actomyosin network is an emergent property of the actomyosin network, rather than driven by upstream signaling.